Peningkatan Kompetensi Konselor dalam Membangun Karakter dan Kesejahteraan Siswa melalui Pelatihan Pemanfaatan Media Digital - Farikha Wahyu Lestari; Eka Sari Setianingsih; Filia Prima Artharina; Latif Anshori Kurniawan (Pelita: Jurnal Pengabdian kepada Masyarakat, 2026)
The program "Guidance and Counseling in the Digital Era: Building Student Character and Psychosocial Well-being" was conducted to enhance the capabilities of Guidance and Counseling (BK) teachers in utilizing digital technology. The initiative was driven by several issues: limited use of technology in BK assessments and administration, a lack of engaging psychoeducational media for students, and the need to improve teachers' skills in delivering services and addressing student issues within the digital space. Solutions provided included training and mentoring on cyber-counseling, digital-based student needs assessment, the creation of digital graphic media, and ethics in digital BK services. Participants were trained to use Google Forms for student needs assessments and to utilize various digital media to create BK services that are more engaging and aligned with student characteristics. The activity involved 35 teachers, comprising 20 from senior high schools (SMA), 5 from vocational high schools (SMK), and 10 from Islamic senior high schools (MA). The program consisted of material presentation, discussions, hands-on practice, independent projects, and evaluation. Evaluation results showed that participants' understanding of information technology use in BK assessments rose from 70% to 83%—a 13-percentage-point increase. The activity successfully enhanced the teachers' knowledge and skills in using technology to support services that are more effective, engaging, and data-driven. Targeted outcomes included improved partner competence, the publication of articles in accredited national journals, and media coverage of the activity.